Exploring the correlation between language medium and academic achievement: a comparative study of the language of learning and teaching (LoLT) and mathematics results in the 2010 Grade 12 National Senior Certificate examinations in the Eastern Cape - Mbude-Shale, Beryl Ntombizanele (Rhodes University, Faculty of Humanities, School of Languages, 2013)
In 2009, of the 68,129 learners who wrote Matric, only 34,731 learners passed. In 2010, there was an increase in the provincial pass rate causing much excitement across the board. The reality was that of the 64,090 learners who wrote, only 37,345 learners passed. In 2010, a result below 50% was recorded for Mathematics and Physical Science nationally (DBE; 2011). Despite efforts by the Education Department to support MSTE; establishing Mathematics and Science schools, NGOs and HEIs giving extra Mathematics and Science support to students and teachers, the offering of Saturday classes and incubation camps, we still get minimal return on investment. This thesis analyses these results against the backdrop of language planning theory, particularly language-in-education policies, pre and post-apartheid. The correlation between language medium and academic performance in language (LoLT) and Mathematics of Grade 12 learners is explored. Worldwide the issue of low achievement in Mathematics by ESL students is of great concern (Cuevas, 1984). The 2004 Systemic Evaluation sample of learners was in Grade 6 then; in 2010 they wrote Grade 12. The purpose of the systemic evaluation was to provide an insight into the levels of learner performance in Maths, Natural Science and LoLT in Grade 6 (IPSER, 2006). A major finding of the IPSER was that language was an important factor related to learner achievement. A major disparity was observed in this research, that although the Eastern Cape performed below the national average in the three subjects evaluated, the learners for whom LoLT was the same as their home language obtained scores that were significantly higher than those whose home language was different from the LoLT. The provincial average for Mathematics was 23.40% compared to the national average of 27.80%. For LoLT the province scored 30.16 against the national score of 38.03%. Of interest in this study is a juxtaposition of the Matric results of this same group of learners in 2010 and see whether issues that came up then are still significant in mitigating achievement in Mathematics and Language (LoLT). Some research studies have been conducted in South Africa (Adler, 1998; Setati, 1996-2002; Moloi, 2006) identifying the vital role language plays in learning Mathematics, especially for English L2 learners. Building on research and findings of academics such as the late Alexander, Ramani, Joseph, Hendricks, Heugh, Dalvit, Webb and Murray, this thesis suggests that a mother-tongue-based-bilingual approach to education should be adopted as a matter of urgency
Keywords: Academic achievement -- Research -- South Africa -- Eastern Cape; Language and education -- Research -- South Africa -- Eastern Cape; Language policy -- South Africa -- Eastern Cape; Mathematics -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Education, Secondary -- South Africa -- Eastern Cape; Matric Learners; Language planning; Mathematics; Policies; Academic performance; Mother-tongue